2018
DOI: 10.1111/1758-2229.12642
|View full text |Cite
|
Sign up to set email alerts
|

Group‐specific environmental sequencing reveals high levels of ecological heterogeneity across the microsporidian radiation

Abstract: The description of diversity is a key imperative in current biological studies and has been revolutionised by the molecular era that allows easy access to microbial diversity not visible to the naked eye. Broadly targeted SSU rRNA gene amplicon studies of diverse environmental habitats continue to reveal new microbial eukaryotic diversity. However, some eukaryotic lineages, particularly parasites, have divergent SSU sequences, and are therefore undersampled or excluded by the methodologies used for SSU studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 32 publications
4
50
0
Order By: Relevance
“…The metabarcoding approach proposed in this study can be used for The V5 region is flanked by group-conserved sequences that allowed us to design the CM-V5F/CM-V5R primer set with great specificity towards microsporidian ssu rDNA. Indeed, the specificity of our primers seems to be higher than the commonly used V1F/530R pair applied by Williams et al (2018) Percentage of identity Fraction of scores as low or lower than the score being plotted Fraction of scores as low or lower than the score being plotted V5 region of ssu rDNA (Figure 4). However, recently published first sequence data for the two remaining microsporidian lineages-the metchnikovellid Amphiamblys sp.…”
Section: Effectiveness Of Metabarcoding Microsporidia and Their Hostsmentioning
confidence: 82%
See 2 more Smart Citations
“…The metabarcoding approach proposed in this study can be used for The V5 region is flanked by group-conserved sequences that allowed us to design the CM-V5F/CM-V5R primer set with great specificity towards microsporidian ssu rDNA. Indeed, the specificity of our primers seems to be higher than the commonly used V1F/530R pair applied by Williams et al (2018) Percentage of identity Fraction of scores as low or lower than the score being plotted Fraction of scores as low or lower than the score being plotted V5 region of ssu rDNA (Figure 4). However, recently published first sequence data for the two remaining microsporidian lineages-the metchnikovellid Amphiamblys sp.…”
Section: Effectiveness Of Metabarcoding Microsporidia and Their Hostsmentioning
confidence: 82%
“…The first attempt to use high-throughput sequencing for microsporidian DNA detection was performed by Williams et al (2018).…”
Section: Standard Microsporidia Detection Methods Are Based On Ul-mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study sampling terrestrial nematodes identified 12 distinct microsporidia species, and C. elegans alone has been reported to be infected by seven different species [19,31,35]. Additionally, environmental sampling has identified dozens of novel species [41,42]. Based on the wide diversity of known animal hosts and the specificity of microsporidia species to infect one or several closely related hosts, it has been suggested that the number of microsporidia species equals the number of animal species.…”
Section: What Is the Host Specificity Of Microsporidia?mentioning
confidence: 99%
“…Among more than 30 named species and many other unnamed taxa that were found in amphipod hosts, Dictyocoela is the most common genus with about 10 known species (Bojko & Ovcharenko, 2019;Dimova et al, 2018;Grabner, 2017;Grabner et al, 2015;Kuzmenkova, Sherbakov, & Smith, 2008;Quiles et al, 2019;Slothouber Galbreath, Smith, Terry, Becnel, & Dunn, 2004;Williams, Hamilton, Jones, & Bass, 2018; see Table 1 in Appendix S1). However, the known diversity of Dictyocoela seems to be restricted both geographically and in terms of host range.…”
mentioning
confidence: 99%